Geopolitics - Thick and Complex. A conversation with Gerard Toal - Bachmann, Veit; Toal, Gerad (ERDKUNDE, 2019)
This contribution centres around a conversation with Gerard Toal (Gearóid Ó Tuathail), held at Goethe-University Frankfurt on 25 October 2018 in the context of the closing events of the project AFRASO (Africa’s Asian Options) – a large interdisciplinary project, funded by the German Ministry for Education and Research (BMBF) between 2013 and 2019. The project investigated the heterogeneous spaces of interaction between Africa and Asia and closed with a lecture series, entitled Afrasian Futures, to which Gerard Toal delivered the first lecture in October 2018. In this contribution, we address the role and evolution of critical geopolitical scholarship, focussing in particular on Toal’s latest book, Near Abroad, as well as on wider debates on (trans)regional studies and shifting geopolitical orderings, such as the ones explored as part of the AFRASO project. It starts with an introductory part in form of a brief reflection on the problematic history of and the ongoing unease with geopolitical scholarship in Germany. It then proceeds with sketching out the basic tenets and the evolution of critical geopolitics, whereby it highlights the decisive influence of Gerard Toal’s work. In the following, the three conceptual foundations of geopolitical field, culture and condition are briefly introduced, as laid out in Toal’s book Near Abroad and in the context of his call for thick analysis of geopolitical complexities. After this introductory part, the remainder of this contribution consists of a conversation with Gerard Toal.